2022
DOI: 10.1177/00222429221100186
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellianism in Alliance Partnerships

Abstract: Against a backdrop of limited research focusing on dark-side characteristics in alliances, the authors argue that Machiavellianism in an alliance influences strategies pertaining to gaining new knowledge and using power to achieve better performance effectiveness. They develop a model using theories-in-use procedures and drawing from both Machiavellian intelligence and achievement goal perspectives, which they test in a quasi-longitudinal study of 199 marketing alliances. The results suggest that Machiavellian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
8
0
1
Order By: Relevance
“…Fourth, we study the effects of individual-level DT traits on individual performance outcomes; considering the DT at the team or firm level (Musarra, Robson, and Katsikeas 2023) or examining its effects on team /firm performance (e.g., Mullins, Menguc, and Panagopoulos 2020) was beyond the scope of our research, leaving open questions about the impact of dark salespeople at a higher level of abstraction. Arguably, in complex selling contexts (e.g., Schmitz, Lee, and Lilien 2014), some managers might want to harness the performance advantages associated with the functional aspects of the DT while mitigating the negative social outcomes and long-term performance losses.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we study the effects of individual-level DT traits on individual performance outcomes; considering the DT at the team or firm level (Musarra, Robson, and Katsikeas 2023) or examining its effects on team /firm performance (e.g., Mullins, Menguc, and Panagopoulos 2020) was beyond the scope of our research, leaving open questions about the impact of dark salespeople at a higher level of abstraction. Arguably, in complex selling contexts (e.g., Schmitz, Lee, and Lilien 2014), some managers might want to harness the performance advantages associated with the functional aspects of the DT while mitigating the negative social outcomes and long-term performance losses.…”
Section: Discussionmentioning
confidence: 99%
“…A further 35 were excluded because of the lack of correct contact details. Due to dynamic nature of export activities, we employed a quasi-longitudinal research design to collect data for this study (Musarra et al, 2023). Accordingly, we collected data on process thinking skills, goal orientation and dynamic capabilities at Time 1 and on export venture performance at Time 2.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…As per recent practice adopting a quasi-longitudinal survey research design (e.g. Musarra et al ., 2023), the use of a time lag in data collection (see subsection on Sample and Data Collection below) enables us to rule out alternative causal orderings of the study constructs despite the lack of formal hypotheses pertaining to export venture dynamic capabilities’ performance effects.…”
Section: Conceptual Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that those with high Machiavellian tendencies tend to exhibit a strong desire to acquire wealth and power, often driven by a competitive spirit [49]. They steadfastly pursue wealth and power and unhesitatingly leverage others to achieve their personal goals [48].…”
Section: Anthropomorphism and Machiavellianismmentioning
confidence: 99%